Registers and modes of communication in the ancient Near East: getting the message across - Keimer, Kyle H. ca. 20./21. Jh.; Davis, Gillan (Routledge, Taylor & Francis Group, 2018)
Communicating in the past; connecting with the past / Gillan Davis and Kyle H. Keimer -- Part I. Imperial and court communications -- Introduction to part I -- The disappearance of cuneiform from the West and elites in the ancient near east / Noel Weeks -- Contrasting representations and the Egypto-Hittite treaty / Samuel Jackson -- Text and context: the question of audience for Sennacherib's 'Public' inscriptions / Luis R. Siddall -- Communication and miscommunication in the Southern sky: the Case of Scorpio and the Southern Cross in cuneiform / Wayne Horowitz -- Imperialism and language: observations on bilingual inscriptions from Palmyra / Samuel N.C. Lieu -- Part II. Community communications -- Introduction to Part II -- "Guard it on your tongue!": the Second Rubric in the Deir Alla Plaster texts as an instruction for the oral performance of the narrative / Gareth Wearne -- Juxtaposition and narrative evaluation in Joshua 1-2 / Rachelle Gilmour -- Literature as flexible communication: variety in Hebrew Biblical texts / Ian Young -- The use of paleo-Hebraic script on Jewish revolt coins: a semiotic focus / Rachel Mansfield, Benjamin Overcash, and Stephen Llewelyn -- Part III. Communications between families and individuals -- Introduction to Part III. -- From Dragomans to Babel: the role of interpreters in the ancient near East in the 1st millennium B.C.E. / Peter Zilberg -- Sex, lies and beautiful eyes: divine communication and premarital relations in Sumerian poetry / Louise M. Pryke -- Communication within a dysfunctional family in late antique Egypt / Alanna Nobbs